2021
DOI: 10.3389/fpls.2021.635550
|View full text |Cite
|
Sign up to set email alerts
|

SP3 Protocol for Proteomic Plant Sample Preparation Prior LC-MS/MS

Abstract: Quantitative protein extraction from biological samples, as well as contaminants removal before LC-MS/MS, is fundamental for the successful bottom-up proteomic analysis. Four sample preparation methods, including the filter-aided sample preparation (FASP), two single-pot solid-phase-enhanced sample preparations (SP3) on carboxylated or HILIC paramagnetic beads, and protein suspension trapping method (S-Trap) were evaluated for SDS removal and protein digestion from Arabidopsis thaliana (AT) lysate. Finally, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 53 publications
1
32
0
1
Order By: Relevance
“…A comparative study of the performance of the three methods (FASP, S-TRAP, and SP3), with tissue lysates from the plant Arabidopsis thaliana, revealed total peptide recovery percentages (after digestion) slightly higher with SP3 relative to FASP and a significantly low peptide yield with the S-Trap method. In the same study, SP3 and FASP revealed a greater number of peptide and protein identifications and lower coefficients of variation in protein quantitation compared to the S-Trap method [46]. The superior performance of the method SP3 was also verified in another study that addressed proteomes from bacteria [48].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A comparative study of the performance of the three methods (FASP, S-TRAP, and SP3), with tissue lysates from the plant Arabidopsis thaliana, revealed total peptide recovery percentages (after digestion) slightly higher with SP3 relative to FASP and a significantly low peptide yield with the S-Trap method. In the same study, SP3 and FASP revealed a greater number of peptide and protein identifications and lower coefficients of variation in protein quantitation compared to the S-Trap method [46]. The superior performance of the method SP3 was also verified in another study that addressed proteomes from bacteria [48].…”
Section: Discussionmentioning
confidence: 72%
“…Previous work has shown that the SP3 method performances are similar or even superior to FASP and other proteomic sample preparation methods. The performance of the SP3 method has been shown to be superior, allowing a greater number of peptide and protein identifications, especially from samples with low amounts of protein (<10 µg total protein) [45,46]. The high performance of SP3 has been attributed to the independence of this method from protein molecular weight.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study on ginseng in which such a high number of identified proteins is reported from a wide range of tissues using only one extraction method without fractionation. However, further investigations comparing this method with different MS sample preparations such as single-pot solid-phase-enhanced sample preparation (SP3) [ 21 ], in-StageTip digestion (iST) [ 22 ], and the suspension trapping (S-Trap) filter [ 23 ] using various ginseng tissues might provide a deeper understanding of the sample preparation for ginseng proteomics.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of the sample for the analysis of mass spectrometry plays a determinant role in the quality of the result. The confirmation of the main part of the amino acid sequence depends on the efficiency of the digestion and the recovery of the tryptic peptides [ 26 ]. In our case, the digestion in gel under native conditions, made it possible to recover the necessary fragments to confirm 51.3% of the RBDr.…”
Section: Discussionmentioning
confidence: 99%